Agency, Freedom, and Responsibility in the Early Heidegger - Pedersen, Hans (Christian Hans) (New Heidegger research., 2020)
This book employs Heidegger's work of the 1920s and early 1930s to develop distinctively Heideggerian accounts of agency, freedom, and responsibility, making the case that Heidegger's thought provides a compelling alternative to the mainstream philosophical accounts of these concepts.